2012
DOI: 10.1017/s0033291711002935
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable patterns of medial prefrontal and amygdala activity to face identityversusemotion in bipolar disorder

Abstract: Background Individuals with bipolar disorder demonstrate abnormal social function. Neuroimaging studies in bipolar disorder have shown functional abnormalities in neural circuitry supporting face emotion processing, but have not examined face identity processing, a key component of social function. We aimed to elucidate functional abnormalities in neural circuitry supporting face emotion and face identity processing in bipolar disorder. Method Twenty-seven individuals with bipolar disorder I currently euthym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…In line with previous neuroimaging studies on euthymic BD patients (e.g., Wessa et al, 2007;Robinson et al, 2008;Chen et al, 2010;Keener et al, 2012) our results suggest that right hemisphere dysfunction is not necessarily related to BD symptoms.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with previous neuroimaging studies on euthymic BD patients (e.g., Wessa et al, 2007;Robinson et al, 2008;Chen et al, 2010;Keener et al, 2012) our results suggest that right hemisphere dysfunction is not necessarily related to BD symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…Although only a few previous studies differentiated between symptomatic and euthymic BD patients (e.g., Wessa et al, 2007;Robinson et al, 2008;Chen et al, 2010;Keener et al, 2012), the majority of these studies also found atypical functional hemispheric asymmetries in emotion perception involving the right fronto-amygdala network in symptom free BD patients. For example, Chen et al (2010) reported increased activation in the right amygdala and right orbitofrontal cortex in euthymic BD patients relative to healthy controls during a facial emotion task in which participants were explicitly asked to rate the affective intensity of faces depicting one of six emotion types (happiness, sadness, disgust, fear, surprise, and anger).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Definitely, another target for future investigation should be assessment of the neural correlates of facial emotion processing in BD, whether through event-related potential studies 29,30 or functional neuroimaging. 31,32 …”
Section: Discussionmentioning
confidence: 99%
“…More recent studies demonstrated in adults with bipolar disorder abnormally increased amygdala and medial prefrontal cortex activity(20,21) and abnormally decreased positive bilateral orbitofrontal cortex-amygdala effective connectivity(22) to emotional, especially happy, faces, suggesting a dysregulated amygdala response to these stimuli. These findings may reflect an underlying attentional bias to positive emotional stimuli in bipolar disorder, predisposing to mania.…”
Section: Introductionmentioning
confidence: 99%